2019
DOI: 10.4314/jasem.v23i10.17
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Diversity Study on three Species of <i>Amaranthus</i> namely; <i>A. hybridus L., A. viridis L.</i> and <i>A.spinosus L.</i> from Rivers State, Nigeria

Abstract: A study of morphological and anatomical diversity on three species of Amaranthus in the Amaranthaceae family namely; A. hybridus L., A.viridis L. and A. spinosus L. from the three senatorial district of Rivers state namely; Rivers East (upland), Rivers South East (upland) and Rivers West (coastal region) was studied to examine the diversity that exist even among similar species from different regions. Result obtained from this research showed high rate of diversity. Examination of the tran–sections of blades r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Over the years, many plants are classified based on their flower and fruits which are considered as external morphological structures whose production are usually seasonal, hence limiting their availability for study and proper identification 20 . Currently, there are calls for some novel protocol for proper and easy identification of plants at any season of the year 21 . Plant anatomical studies of the vegetative organs like leaves, roots and stems which may be found at all seasons seem to be a solution to such challenges 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many plants are classified based on their flower and fruits which are considered as external morphological structures whose production are usually seasonal, hence limiting their availability for study and proper identification 20 . Currently, there are calls for some novel protocol for proper and easy identification of plants at any season of the year 21 . Plant anatomical studies of the vegetative organs like leaves, roots and stems which may be found at all seasons seem to be a solution to such challenges 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are calls for some novel protocol for proper and easy identification of plants at any season of the year 21 . Plant anatomical studies of the vegetative organs like leaves, roots and stems which may be found at all seasons seem to be a solution to such challenges 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, a crucial subject of discussion among Plant taxonomists for years now is the problem of accurate plant identification and classification: a challenge which abounds among species of family Euphorbiaceae too [1,13,14]. For years now, a lot of plants are classified based on their flora and fruits which are considered as external morphological features whose production are seasonal, hence limiting their availability for study and proper identification [15,16]. Currently, there are quest for some novel protocols for easy and better identification of plant at any time or season of the year [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For years now, a lot of plants are classified based on their flora and fruits which are considered as external morphological features whose production are seasonal, hence limiting their availability for study and proper identification [15,16]. Currently, there are quest for some novel protocols for easy and better identification of plant at any time or season of the year [15,16]. Some method suggested includes: the use of cytological, anatomical, molecular and epidermal systematics from the leaves, roots and stems which are not time bound [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation